MICROANALYSIS PEMBENTUKAN KRISTAL CALSIUM SULFAT PADA PIPA BERALIRAN LAMINER DENGAN PARAMETER LAJU ALIR - Mangestiono, Wiji (Universitas Diponegoro, 2011)
Abstract Â Gypsum (CaSO4. 2H2O) scaling inside pipe is very problematic for industries since it causes narrowing of pipe diameter, thickening of heat transfer surfaces, lenghthening the process time and finally increase the cost of production. It is therefore necessary to prevent the occurance of gypsum scaling in a piping system. This report describes an experiment on gypsum scale formation utilizing CaCl2.2H2O and Na2SO4 solutions to form gypsum ( CaSO4. 2H2O). The concentration the calcium ions selected was 3,500 ppm. The experiment was carried out a pipe with several coupons made of copper representing common pipe material used in industry. Flowrate of gypsum solution as one of process parameters for gypsum scaling was varied: 30, 40 andÂ 50 ml/minuteÂ respectively. In addition, Cu2+ as impurities was aded into the solution : 5 and 10 ppm respectively. In adition, a microanalysis on the scale was also caried out using EDAX. The mass of the scale formed was calculated in order to determine the rate of the gypsum scale growth. Keywords : flowrate, gypsum, impurities, piping system.